Du teikei à l’AMAP, un modèle acculturé - Jean Lagane (Développement Durable et Territoires)
After two ethnological fieldworks completed in France and Japan, this article deals with the French system of Community Supported Agriculture - AMAP - and its Japanese inspiration counterpart, the Teikei system built upon local solidarity-based partnerships between farmers and members. Constantly evolving, the growing process of agriculture one-shot sale circuits and the way they are received in other cultures recalls the necessity to tune with the reality of these societies, their history, their institutional and cultural traditions as well as their crises and dynamics. The analysis emphasizes the complexity of the acculturation process related with points of convergence and discrepancy.